Financial accounting and reporting 2 - Mohamad Ariff, Akmalia; Alfan, Ervina; Abdullah, Mazni; Sapiei, Noor Sharoja; Puat Nelson, Sherliza; Rosli, Mohamad Hafiz (Oxford University Press, 2017)
This book caters for degree students pursuing accounting and business courses at institutions of higher learning. Aligned with the framework-based teaching of International Financial Reporting Standards (IFRS) pedagogy, this comprehensive book contains 10 chapters that build on the knowledge and skills introduced in Financial Accounting and Reporting 1. It exposes students to more complex items, while exploring topics such as property, plant and equipment, inventory, intangible assets, investment property, biological assets, financial instruments, leases, deferred tax, introduction to group accounts, as well as impairment of assets.